2021
DOI: 10.3390/molecules26010240
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Impact Strength of Polylactide Blends with a Thermoplastic Elastomer Compatibilized with Biobased Maleinized Linseed Oil for Applications in Rigid Packaging

Abstract: This research work reports the potential of maleinized linseed oil (MLO) as biobased compatibilizer in polylactide (PLA) and a thermoplastic elastomer, namely, polystyrene-b-(ethylene-ran-butylene)-b-styrene (SEBS) blends (PLA/SEBS), with improved impact strength for the packaging industry. The effects of MLO are compared with a conventional polystyrene-b-poly(ethylene-ran-butylene)-b-polystyrene-graft-maleic anhydride terpolymer (SEBS-g-MA) since it is widely used in these blends. Uncompatibilized and compati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…The average contact angle value for neat PLA was about 97° ( Figure 2 ), which is in good agreement with previously reported values in the literature [ 26 , 27 ].…”
Section: Resultssupporting
confidence: 91%
“…The average contact angle value for neat PLA was about 97° ( Figure 2 ), which is in good agreement with previously reported values in the literature [ 26 , 27 ].…”
Section: Resultssupporting
confidence: 91%
“…Regarding PLA (Figure 11a,b), smooth surface without roughness was observed, due to the absence of plastic deformation, characteristic of fragile fracture, as observed in the impact strength and tensile experiments [37,38,[61][62][63].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 70%
“…Regarding thermal analysis, it was observed by DSC that the BioPE addition as well as compatibilizing agents increase the degree of crystallinity of neat PLA, increase the macromolecular chains, and provide significant improvement in thermal stability, mainly in parameter TD99.9%, as observed by TG. The mechanical and thermomechanical properties demonstrated that the compatibilizing agents improve the interactions among bioblends phases, with property increases such as elongation at break, tensile strength, impact strength, and unchanged Regarding PLA (Figure 11a,b), smooth surface without roughness was observed, due to the absence of plastic deformation, characteristic of fragile fracture, as observed in the impact strength and tensile experiments [37,38,[61][62][63].…”
Section: Discussionmentioning
confidence: 85%
“…In Figure 8 a, it was noted that all compositions showed three main events during heating. The first event is a variation from baseline, which is related to the Tg of PLA, around 62.5 °C [ 46 , 47 ], a value above room temperature, confirming its brittle characteristic, observed in the impact test. The blends PLA/EE-g-GMA and PLA/POE-g-GMA also presented this Tg event, however, without significant variations.…”
Section: Resultsmentioning
confidence: 73%